Effect of Virtual Reality–Based Therapies on Lower Limb Functional Recovery in Stroke Survivors: Systematic Review and Meta-Analysis - Wenxin Lu; Minglei Shi; Lu Liu; Shu Wang; Wuquan Deng; Yu Ma; Yanzhong Wang (Journal of Medical Internet Research)
Abstract BackgroundVirtual reality (VR) therapy has gained attention as a promising intervention in stroke rehabilitation, particularly for its potential to enhance motor function and promote neuroplasticity. However, its specific effects on balance, mobility, and gait remain underexplored. ObjectiveThis review aims to provide a comprehensive evaluation of the effectiveness of VR therapy on the recovery of lower limb function in stroke survivors. MethodsRandomized controlled trials comparing VR therapy with conventional therapy were eligible for inclusion. All studies were identified through databases, such as MEDLINE, Embase, PubMed, Cochrane Library, Web of Science, and PsycINFO (up to July 2024). The primary outcomes included balance, assessed using the Berg Balance Scale (BBS), and mobility, measured with the Timed Up and Go Test (TUG) and 10-Meter Walk Test (10-MWT). Secondary outcomes included gait parameters (stride length and step length), the Functional Reach Test (FRT), the Dynamic Gait Index (DGI), and the Falls Efficacy Scale-International (FES-I). RevMan version 5.4 (The Cochrane Collaboration) software was used for the meta-analysis. ResultsA total of 2145 studies were screened, and 24 randomized controlled trials that met the inclusion criteria were included, involving 768 participants. Meta-analysis results showed that VR therapy, compared to conventional therapy, significantly improved BBS (mean difference [MD] 3.29, 95% CI 0.52-6.06; PPPPPPPPPPP ConclusionsLong-term VR-based therapies are more effective in improving functional ability after stroke. VR therapy has demonstrated significant potential for enhancing lower limb recovery, especially when applied with frequencies of ≥20 sessions.